The effects of acute exercise applied to the lower extremity with blood flow restriction on perceived exertion, blood lactate level and cardiovascular responses - Seda Yalcin (ROL Spor Bilimleri Dergisi)
This study, it was aimed to compare the effects of acute squat exercise applied to the lower extremities with and without blood flow restriction (BFR) on post-exercise cardiovascular responses, blood lactate level and perceived exercise intensity. The study consisted of 30 (age 19.83±1.31 years) healthy young male participants. Participants were randomly divided into an experimental (BFR+ resistance exercise) and a control (only performing resistance exercise). In 90% of their 1 Repeat maximum (RM)’s, they performed the squat exercise for a total of six sets, with two repetitions in each set and a 3-minute rest interval between sets. Blood lactate values, blood pressure and perceived exertion degrees of the groups were taken before and after exercise. Repeated measures analysis of variance (Repeated Measures ANOVA) and independent sample t-test were used to analyze the data. In statistical analysis, the significance level was accepted as p<0.05. According to the research results, significant differences were obtained in favor of the resistance exercise group applied with blood flow restriction in the blood pressure, lactate and perceived difficulty levels of the exercise. Using the BFR method in some selected exercises can be recommended as a complementary program to the traditional method.